Adopting Ambulatory Breast Cancer Surgery as the Standard of Care in an Asian Population - Yvonne Ying Ru Ng; Patrick Mun Yew Chan; Juliana Jia Chuan Chen; Melanie Dee Wern Seah; Christine Teo; Ern Yu Tan (International Journal of Breast Cancer)
Introduction. Ambulatory surgery is not commonly practiced in Asia. A 23-hour ambulatory (AS23) service was implemented at our institute in March 2004 to allow more surgeries to be performed as ambulatory procedures. In this study, we reviewed the impact of the AS23 service on breast cancer surgeries and reviewed surgical outcomes, including postoperative complications, length of stay, and 30-day readmission. Methods. Retrospective review was performed of 1742 patients who underwent definitive breast cancer surgery from 1 March 2004 to 31 December 2010. Results. By 2010, more than 70% of surgeries were being performed as ambulatory procedures. Younger women (P<0.01), those undergoing wide local excision (P<0.01) and those with ductal carcinoma-in situ or early stage breast cancer (P<0.01), were more likely to undergo ambulatory surgery. Six percent of patients initially scheduled for ambulatory surgery were eventually managed as inpatients; a third of these were because of perioperative complications. Wound complications, 30-day readmission and reoperation rates were not more frequent with ambulatory surgery. Conclusion. Ambulatory breast cancer surgery is now the standard of care at our institute. An integrated workflow facilitating proper patient selection and structured postoperativee outpatient care have ensured minimal complications and high patient acceptance.